2016
DOI: 10.1074/jbc.m116.744953
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cβ-TRAX Association Is Required for PC12 Cell Differentiation

Abstract: When treated with nerve growth factor, PC12 cells will differentiate over the course of several days. Here, we have followed changes during differentiation in the cellular levels of phosphoinositide-specific phospholipase Cβ (PLCβ) and its activator, Gα, which together mediate Ca release. We also followed changes in the level of the novel PLCβ binding partner TRAX (translin-associated factor X), which promotes RNA-induced gene silencing. We find that the level of PLCβ increases 4-fold within 24 h, whereas Gα i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…When PC12 cells are treated with nerve growth factor, proliferation ceases and neurites form (31, 32). Our previous studies show that the levels of PLCβ1 increase dramatically in the first 24 h, long before the levels of Gα q rise (1). Thus, our studies give rise to a model in which the bolus of PLCβ1 produced at the onset of differentiation binds to CDK16 to prevent entry into the S phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When PC12 cells are treated with nerve growth factor, proliferation ceases and neurites form (31, 32). Our previous studies show that the levels of PLCβ1 increase dramatically in the first 24 h, long before the levels of Gα q rise (1). Thus, our studies give rise to a model in which the bolus of PLCβ1 produced at the onset of differentiation binds to CDK16 to prevent entry into the S phase.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was carried out as previously described (1) using the following primary antibodies: PLCβ1 (D‐8; Santa Cruz Biotechnology, Dallas, TX, USA), Gα q (E‐17; Santa Cruz Biotechnology), β‐actin (Abcam, Cambridge, United Kingdom), PO4‐Ser10‐p27 Kip1 (Abcam), and glyceraldehyde 3‐phosphate dehydrogenase (Abcam).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, C3PO competes for the same site on PLCβ as Gαq and increasing its cellular levels quenches calcium signaling mediated through Gαq receptors [6][7][8]. It is notable that increasing the level of activated Gαq by transfection or stimulation, will result in dissociation of PLCβ from C3PO and allow C3PO to promote RNA-induced silencing [7,8].In previous studies, we found that cytosolic PLCβ1 is required for differentiation of PC12 cells [9]. PC12 cells are a widely used model for neuronal cell differentiation [10].…”
mentioning
confidence: 91%